Redox and electrically driven changes in materials for reversible solid oxide fuel/electrolyser cells - Natoli Gutiérrez, Alejandro (2021)
This project is focused on the study of dynamic changes in the composition, structure, microstructure and electrochemical properties of solid electrolyte cell materials, for prospective operation in reversible electrolyzer/fuel cell modes, at high temperatures, as well as the corresponding changes in performance. Thus, the main objective of this thesis was to develop novel materials and concepts for enhanced tolerance to electrochemical reversibility and self-healing approaches to revert ageing, seeking materials with oxygen storage capacity, ability to block the cation diffusion and related phenomena and also with the capacity to capture diffusing contaminants. An introduction of the fuel cell, seeking its employ as reversible system and associated degradation issues of the fuel cell elements were overviewed in Chapter 1, based on relevant literature. Main materials employed as fuel cell components and some possible mitigation strategies in order to prevent the severe effects of degradation also were reviewed in this chapter. In Chapter 3 one studied composition changes and corresponding impact on redox stability, defect chemistry, transport properties, thermochemical expansion and other relevant properties of yttria partially stabilized zirconia with co-additions of Mn, intended for application as buffer layers. The design of these compositions was guided by analysis of the impact of Mn and redox conditions on stability and transport properties. In Chapter 4 one studied [(ZrO2)0.95(Y2O3)0.05]0.85(MnO1.5)0.15] buffer layers, processed by direct firing of powder mixtures, for prospective applicability as buffer layer at the oxygen electrode/electrolyte interface of solid electrolyte cell, in order to minimize the risks of degradation and delamination. The generic firing schedule was selected by the Taguchi planning and the contribution of each individual factor in the properties of the materials were discussed. Similarly, samples with composition [(ZrO2)1-x(Y2O3)x]1-y(PrO1.5)y] (x≤0.05; 0.05≤y≤0.15) were prepared considering a model system for sealing strategies, oxygen storage and the ability to eliminate the delamination in SOEC mode (Chapter 5). Transport properties, thermochemical expansion and other relevant properties were studied for its employ as buffer layer in the oxygen/electrolyte interface using Taguchi planning to select the firing condition. Strontium titanate-based materials were prepared by partial substitution of La by Sr in the A site and Mo by Ti in the B site. One studied the impact of these substitutions on structure, microstructure, electrical transport properties, thermochemical and dilatometric behavior, and a defect chemistry model was proposed. The detailed studied carried out in chapters 3-6 provided useful information for the preparation of fuel cells and the preliminary electrochemical test reported in the chapter 7. This chapter includes detailed studied about: a) reactivity between fuel electrode based materials and buffer layer (YCTO), b) deposition of fuel electrodes onto traditional 8YSZ electrolyte with and without modification of cell performance by CGO and Ni-CGO infiltration and/or application of YCTO buffer layer with electrochemical preliminary screening, c) preliminary screening of the fuel cell performance with the buffer layers prepared in chapter 3-5, employing commercial LSM electrodes.